A biomechanical testing system to determine micromotion between hip implant and femur accounting for deformation of the hip implant: Assessment of the influence of rigid body assumptions on micromotions measurements. (February 2017) - Leuridan, Steven; Goossens, Quentin; Roosen, Jorg; Pastrav, Leonard; Denis, Kathleen; Mulier, Michiel; Desmet, Wim; Vander Sloten, Jos
Abstract: Background: Accurate pre-clinical evaluation of the initial stability of new cementless hip stems using in vitro micromotion measurements is an important step in the design process to assess the new stem's potential. Several measuring systems, linear variable displacement transducer-based and other, require assuming bone or implant to be rigid to obtain micromotion values or to calculate derived quantities such as relative implant tilting. Methods: An alternative linear variable displacement transducer-based measuring system not requiring a rigid body assumption was developed in this study. The system combined advantages of local unidirectional and frame–and–bracket micromotion measuring concepts. The influence and possible errors that would be made by adopting a rigid body assumption were quantified. Furthermore, as the system allowed emulating local unidirectional and frame–and–bracket systems, the influence of adopting rigid body assumptions were also analyzed for both concepts. Synthetic and embalmed bone models were tested in combination with primary and revision implants. Single-legged stance phase loading was applied to the implant – bone constructs. Findings: Adopting a rigid body assumption resulted in an overestimation of mediolateral micromotion of up to 49.7 μm at more distal measuring locations. Maximal average relative rotational motion was overestimated by 0.12° around the anteroposterior axis. Frontal and sagittal tilting calculations based on a unidirectional measuring concept underestimated the true tilting by an order of magnitude. Interpretation: Non-rigid behavior is a factor that should not be dismissed in micromotion stability evaluations of primary and revision femoral implants. Highlights: Implant and bone motion can be measured simultaneously at several locations. Non-rigid behavior has a major influence on implant stability measurement results. Under a rigid body assumption, distal micromotion was overestimated by up to 49.7 μm. Under a rigid body assumption, relative rotational motion was overestimated by up to 0.12°.